PENINGKATAN KOMPETENSI GURU-GURU SMP SOLOK SELATAN MELALUI PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KONTEKSTUAL DENGAN PENDEKATAN SAINTIFIK - Hufri Hufri; Harman Amir (Fakultas MIPA Universitas Negeri Padang, 2018)
In the education sector of South Solok District, it is still lagging behind other regions in West Sumatera, this can be seen from the results of the UN rankings in 2016 which is ranked 16th out of 19 cities / districts in West Sumatera. Based on observations and discussions conducted on some teachers and principals, information is obtained that this is because in learning students are more likely to wait what is delivered by teachers or learning is still concentrated on the teacher. Then in learning the teacher has not used various media of learning. The media used can not accommodate the fact of the student's daily condition. This service activity aims to improve the competence of teachers of South Solok SMP in developing contextual based learning media with scientific approach. Target to be achieved is the improvement of competence of teachers and media of learning. To achieve the objectives and targets set, the methods used consist of six stages: observation stage, orientation and discussion stage, preparation stage, implementation stage, monitoring and evaluation stage and final stage of data analysis and report generation. Based on data analysis of pretest and posttest results, obtained an increase of average value from pretest that is 43,07 become 47,42 at postest. Furthermore, to know the difference between the two values of pretest and postes paired t test, obtained the results of significance 0.000 < 0.05, so it can be concluded that there is a difference between pretest results with postes. Furthermore, based on the questionnaire given at the end of the training activities, the results obtained that the participants said this activity is very useful and related to the subjects taught in schools